The Significance of Buildings in Terms of a Christian Presence in the Community. (2nd July 2016) - Inge, John
Abstract : Arguing from a biblical perspective, this article proposes that place is a crucial part of human experience and God's way with the world, that there is a three way relationship between God, people and place in which all three are crucial. Engaging with the Christian tradition, it suggests that churches can be thought to operate 'sacramentally' as fractions set apart to represent the truth that all time and space are God's. They witness just by being there but there is a pressing need for them to be used more and more in the service of the communities in which they stand as well as for worship of the Living God, and thus to symbolise the second as well as the first Great Commandment.